Heat transfer enhancement and pressure loss in a plate-fin heat exchanger with V-shaped oblique wavy surface. (November 2020) - Gong, Jiaming; Onishi, Junya; He, An; Kametani, Yukinori; Hasegawa, Yosuke; Shikazono, Naoki
Hightlight: Moderate oblique angle and large amplitude are beneficial for heat transfer augmentation. Large oblique angle and small amplitude are beneficial for relieving pressure loss. The optimal geometry which balances heat transfer enhancement and pressure loss is obtained by adopting an acute oblique angle close to 75 o with large amplitude, and its Colburn factor j and goodness factor j/f increased by 150% and 16% at Re = 500, respectively, compared with the plain channel. Abstract: Numerical investigations on the heat transfer and pressure loss of a plate-fin heat exchanger with V-shaped oblique wavy surface have been conducted. The effects of pointing direction of V shape, oblique angle and wave amplitude are systematically studied to find out the geometry with the best thermal-hydraulic performance. It is found that the oblique wavy surface induces two pairs of counter rotating secondary flows which significantly enhance heat transfer irrespective of the pointing direction of the V shape. Meanwhile, the oblique wavy surface with the V shape pointing downstream shows relatively low pressure loss. It is also found that moderate oblique angle and large amplitude are beneficial for heat transfer augmentation, while oblique angle near 75 o and small amplitude are beneficial for relieving pressure loss. The optimal geometry which balances heat transfer enhancement and pressure loss is obtained by adopting an acute oblique angle close to 75 o with large amplitude, and its Colburn factor j and goodness factor j/f increased by 150% and 16% at Re = 500, respectively, compared with the plain channel.